Role of the Autonomic Nervous System in Mechanism of Energy and Glucose Regulation Post Bariatric Surgery - An, Zhibo; Wang, Haiying; Mokadem, Mohamad (Frontiers in Neuroscience, 2021)
Sleeve gastrectomy and Roux-en-Y gastric bypass (RYGB) remain the most effective and durable therapies facing the growing obesity pandemic and its associated metabolic disorders. The traditional classifications of bariatric surgeries labeled them as “restrictive”, “malabsorptive”, or “mixed” types of procedures depending on the anatomical rearrangement of each one of them. This conventional categorization of bariatric surgeries assumed that the “restrictive” procedures induce their weight loss and metabolic effects by reducing gastric content and therefore having a smaller reservoir. Similarly, the “malabsorptive” procedures were thought to induce their main energy homeostatic effects from fecal calorie loss due to intestinal malabsorption. Observational data from human subjects and several studies from rodent models of bariatric surgery showed that neither of those concepts is true. Rather, neuro-hormonal mechanisms have been postulated to underlay the physiologic effects of those two most performed bariatric procedures around the world. In this review, we focus on the role of the autonomic nervous system plays- through its parasympathetic and sympathetic branches- in regulating weight balance and glucose homeostasis after sleeve gastrectomy and RYGB.